2017
DOI: 10.1007/s40708-017-0069-3
|View full text |Cite
|
Sign up to set email alerts
|

Emotion recognition based on EEG features in movie clips with channel selection

Abstract: Emotion plays an important role in human interaction. People can explain their emotions in terms of word, voice intonation, facial expression, and body language. However, brain–computer interface (BCI) systems have not reached the desired level to interpret emotions. Automatic emotion recognition based on BCI systems has been a topic of great research in the last few decades. Electroencephalogram (EEG) signals are one of the most crucial resources for these systems. The main advantage of using EEG signals is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(39 citation statements)
references
References 30 publications
1
33
0
Order By: Relevance
“…For instance, according to Zhang et al in [ 6 ], there were ten participants and they used eight electrodes, whereas in our study, there were nine participants and we used sixteen channels. In [ 12 ], the number of channels of the EEG was thirty-two with twenty participants whereas our data came from sixteen channels. According to Ahmad et al in [ 13 ], the number of channels was 128 with eight healthy participants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, according to Zhang et al in [ 6 ], there were ten participants and they used eight electrodes, whereas in our study, there were nine participants and we used sixteen channels. In [ 12 ], the number of channels of the EEG was thirty-two with twenty participants whereas our data came from sixteen channels. According to Ahmad et al in [ 13 ], the number of channels was 128 with eight healthy participants.…”
Section: Discussionmentioning
confidence: 99%
“…Isa et al in [ 11 ], showed 70.08% KNN accuracy as the highest classification with Minkowski distance computation. Two classified conditions, which are represented in positive and negative emotions collected by EEGÖzerdem and Polat in [ 12 ], indicated 77.14% accuracy for multilayer perceptron neural network (MLPNN) and 72.92% for K-Nearest Neighborhood (KNN). Based on linear and nonlinear features derived from EEG, cognitive activity and resting-state conditions were classified by applying SVM and 92.1% was achieved applying nonlinear features whereas 87.5% of SVM was observed applying linear features [ 13 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Time-frequency analysis is based on the spectrum of EEG signals, and the energy, power, power spectral density and differential entropy (DE) [ 17 ] of a certain subband are utilized as features. Short-time Fourier transform (STFT) [ 18 , 19 ], Hilbert-Huang transform [ 20 , 21 ] and discrete wavelet transform [ 22 , 23 , 24 , 25 ] are the most commonly used techniques for spectral calculation. Higher frequency subbands, such as Beta (16–32 Hz) and Gamma (32–64 Hz) bands, have been verified to outperform lower subbands in emotion recognition [ 3 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Özerdem and Polat used EEG signal, discrete wavelet transform and machine learning techniques (multilayer perceptron neural network -MLPNN, and k-nearest neighbors -kNN algorithms) [57].…”
Section: Physiological Signalsmentioning
confidence: 99%